Pengaruh Harga Lokasi Dan Online Customer Review Terhadap Keputusan Pembelian Pada Hart Chicken Exprezz Surabaya - Aditya Rizky Sahari; Rifda Fitrianty; M Azizul Khakim; Agung Dwi Nugroho (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This test was conducted by researchers with the intention if there is still a correlation regarding price, place and opinions given by consumers based on experience when making a purchase transaction with consumer decisions when making a return transaction at Hart Chicken Exprezz Surabaya. The test was conducted using a quantitative method, namely the multiple linear regression analysis approach. Researchers have created a questionnaire that has been given by all consumers with a total of 97 responses to complete the test data. Finding the number studied during the test, namely by means of units for the Price variable still has a very significant correlation by consumer decisions when making a purchase transaction with a significance of 0.012, location also has results that are still related and significant by consumer decisions when making a purchase transaction with a significant result of 0.024 and the experience of consumers who have provided responses also has a significant influence by consumer decisions when making a purchase transaction with a significant amount of 0.000. Furthermore, the simultaneous test shows that the three variables have a correlation and are significant by consumer decisions when making a purchase transaction, having a calculated F of 252.216 and a significance of 0.000. Then, a retest using a coefficient of determination (R²) of 89.1% revealed that price, location, and online customer reviews had an 89.1% influence on consumer purchasing decisions. This suggests that price, location, and the experiences of consumers who had previously purchased at Hart Chicken Exprezz Surabaya had a positive impact, increasing purchasing decisions.